ANALISIS PENYELESAIAN TINDAK LANJUT HASIL PEMERIKSAAN BPK PADA PEMERIKSAAN KINERJA ATAS KEGIATAN APIP INSPEKTORAT KABUPATEN BARITO TIMUR - Josmar Lambok Banjar Nahor; Ade Adriani; Wahyudin Nor (Department of Accounting, Faculty of Economics & Business, 2021)
AbstrackThe purpose of this research is to reveal the obstacles in the completion of the follow-up of audit the BPK of the performance audit of APIP Inspectorate of East Barito Regency. This research uses qualitative methods with a case study approach which was carried out at the Inspectorate of Barito Timur, Central Kalimantan from September to December 2018. The result of the analysis reveal that the obstacles in completing this follow-up are caused by several internal aspects, including: 1) human resources, the lack of ASN, the mismatch of the educational background of the ASN personnel, and the lack of teamwork 2) leadership, the leader has not yet prepared a work plan for completion of the follow-up to the BPK audit results on performance audit of APIP activities, formed a special team, coordinates, controls, never holding a special meeting to discuss BPK findings on the completion of the BPK audit follow - up on the performance audit APIP, there is no formation of a special team that handle the completion of the follow-up results of the BPK audit on the performance audit of APIP, there is no instruction from the leadership to complete the follow-up of the BPK audit results on the APIP performance audit. 3) Work environment, non-physical work environment, a work culture that has not been optimal , encourages completion of follow-up. Meanwhile, the physical work environment, such as the availability of facilities and facilities is still limited.Research on these three aspects is very useful to understand how to optimize the acceleration of the completion of the follow-up of the inspection results, especially in the Inspectorate of East Barito Regency APIP